Komunikasi Interpersonal dan Iklim Komunikasi Organisasi Pada Divisi Redaksi Harian Radar Banjarmasin - Musliadi (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2020)
Interpersonal communication of Radar Banjarmasin employees can support employee performance, this can be seen from openness, empathy, support, a sense of positivity and equality even though it is more semi-cultural by instilling an atmosphere of humor and only a small part occurs intensively among employees in interpersonal communication on the basis of ties. friendship, in the valence of self disclosure, builds positive strength semi-culturally to create a good working atmosphere. However, the research facts found that the intimacy of employees' self-disclosures is shallow, this is more often the case, is limited to the communication of colleagues in the team. Meanwhile, the communication climate of the Daily Editorial Division of Radar Banjarmasin is seen from the elaboration of the five dimensions of organizational communication climate, namely supportiveness, participation in decision making, trust, openness, and high performance goals. Although the dimension of openness is not too strong because there are some employees who are not always open with their superiors whether they are complaints, ideas, suggestions, or criticism. This is evident from the number of employees who grapevine both in the office and outside the office.